Childhood emotional experience within the family relation to the current partnership and the desire to have children - Tretjakova I.; Mihailova S. (SHS Web of Conferences, 2016)
The paper studied the relationship between emotional experience in childhood and the quality of the existing partnerships. With a questionnaire, specifically designed by I. Tretjakova, 221 respondents aged 20–40 years were interviewed. The study leads to the conclusion that a positive emotional experience in childhood helps to develop emotionally healthy environment in marriage (including unregistered or civil partnership), and creates the desire to have children, and vice versa, emotionally negative experience in childhood disturbs the creation of an emotionally favourable environment for marriage and causes conflicts in relationships, provokes desire to divorce, but it cannot be stated that more interpersonal problems are the cause of lower birth rates than there are at fewer marital problems. The study confirms that a stable marriage can be an important factor contributing to the woman's desire to have children Thus it can be assumed that development of emotion regulation skills could be a contributing factor in order to form successful partnerships and promote birth of more children in the family context.